2018
DOI: 10.1093/jac/dky111
|View full text |Cite
|
Sign up to set email alerts
|

Novel plasmid-mediated colistin resistance gene mcr-7.1 in Klebsiella pneumoniae

Abstract: We identified a novel plasmid-mediated colistin resistance gene named mcr-7.1 in K. pneumoniae in China. The prevalence of mcr-7.1 in various species of human and animal origin needs to be investigated immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
196
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(209 citation statements)
references
References 25 publications
4
196
1
8
Order By: Relevance
“…it has to be considered that although we did not find mcr-2 in our study, up to 8 genetic 296 determinants for colistin resistance have been described [60][61][62]. Therefore, a search for 297 more genetic determinants should be conducted to better understand the epidemiology 298 of colistin resistance in poultry from Ecuador.…”
mentioning
confidence: 69%
“…it has to be considered that although we did not find mcr-2 in our study, up to 8 genetic 296 determinants for colistin resistance have been described [60][61][62]. Therefore, a search for 297 more genetic determinants should be conducted to better understand the epidemiology 298 of colistin resistance in poultry from Ecuador.…”
mentioning
confidence: 69%
“…coli that carried the colistin resistance gene (mcr-1) (Liu et al, 2016) were identified. Until now, 9 subtypes of mcr (Liu et al, 2016;Xavier et al, 2016;AbuOun et al, 2017;Borowiak et al, 2017;Carattoli et al, 2017;Yin et al, 2017;Wang X. et al, 2018;Yang et al, 2018;Carroll et al, 2019) and 21 subtypes of bla NDM have been published with papers. The discovery of these two types of resistance genes that can be horizontally transferred via plasmids has made researchers aware of the post-antibiotic era.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the following four genes were described: (i) mcr-3 in E. coli from pigs in China (Yin et al, 2017); (ii) mcr-4 in Salmonella and E. coli isolated from pigs in Italy, Spain, and Belgium (Carattoli et al, 2017); (iii) mcr-5 in Salmonella Paratyphi B from poultry in Germany (Borowiak et al, 2017); and (iv) mcr-6 (originally termed mcr-2.2 variant) in Moraxella pluranimalium from pigs at slaughter in the United Kingdom (AbuOun et al, 2018). The next year, mcr-7 was detected in Klebsiella pneumoniae from chickens and mcr-8 in K. pneumoniae from pigs, chickens, and humans in China Yang et al, 2018). In 2019, the mcr-9 gene was described in CT-susceptible Salmonella Typhimurium isolated from a patient in the United States in 2010.…”
Section: Introductionmentioning
confidence: 99%